(3GdEfHGA HfHC GdCfHjGA Ydjge GdUdGI hGdSdGes - (3eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj , TgGH GdOjf CHh YHO Gddg,J (B454 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eHOF cd TF hhQGKg gPG cJGH CLeY ajg HeTjFJg hYhfg LedkG ef CfHGA GdCfHjGA hJhGQjN GdNdaGA hhdGjGJ Gdedhc hGdCeQGA s
(3BNQgG (B:s
(3BNQI ef JQLeI CHj GdYHGS GdfGUQ dOjf Gddg CejQ GdeDefjf GdeJhai SfI (B622(3g` hBNQ eG ajg (B: (3heGJ hbO CNP GdHjYI dhdOg GdWGgQ GdGYR dOjf Gddg GfJgi GdehLhO ef JGQjN GdbVGYi QMeg Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HBNQgG CQHY hQbGJ HNW MOjKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eTQa YHO GdcQje GdNGUI HJYR s
Keywords: (3GdJGQjNs